Need-relevant parenting and Peruvian high school students' affect and academic achievement : the differential role of need satisfaction and need frustration - Matos Fernández, Lennia (2025)
This study examined the mediating role of need-related experiences in the relation between need supportive and need thwarting parenting, positive and negative affect and grades among 304 high school students (M age = 14.91; SD age = 0.91; 53% female) from a Peruvian private school. Grounded in Self-Determination Theory (SDT) and considering latest empirical findings, a dual pathway, involving a bright and dark path, was hypothesized with need satisfaction and frustration mediating the relation from, respectively, need supportive parenting to positive affect and grades and from need thwarting parenting to negative affect. Using structural equation modeling we found evidence for the proposed mediation model, with the exception that academic achievement was predicted directly by parental need support. The present results highlight the importance of fostering students’ psychological needs to promote optimal emotional and academic functioning through parents’ need support.